Morphological Features of the Pecten Oculi in the Common Kestrel (Falco tinnunculus) - Kilinç, Bahadır; Toprak, Burhan; Yüksel, Süleyman; Kandir, Emine Hesna; Koçak, Gökhan (Wiley, 2025)
ABSTRACTThis study aimed to investigate the macroscopic, light microscopic (LM) and scanning electron microscopic (SEM) characteristics of the pecten oculi in common kestrels (Falco tinnunculus). A total of six eyeballs from three common kestrels were used as the study material. The examination revealed that the bulbus oculi was spherical in shape and its diameter exceeded the axial‐global length. In the equatorial section of the eyeball, the pecten oculi were observed to be situated on the retina layer where the optic nerve enters the eyeball, showing a posterior‐to‐anterior distribution. The pecten oculi appeared dark brown, with a convoluted structure, comprising approximately 15–17 vascular folds. Scanning electron microscopic examination revealed dense capillary vascular folds on the surface of the pecten oculi. Within these capillary vessels, a few hyalocytes were noted, and melanocytes were found at the edges of the folds. Light microscopic examination detected numerous large, medium and small diameter vessels within the folds of the pecten oculi, especially at the periphery of the folds and the apical parts of the pecten oculi. The findings of this study were compared with the morphological characteristics of the pecten oculi in other bird species, revealing both similarities and differences.
Keywords: Microscopy, Electron, Scanning; Animals; Eye; Falconiformes; Retina